Production of Complex Multiantennary N-Glycans in Nicotiana benthamiana Plants(1)([W])([OA]) - Nagels, Bieke (American Society of Plant Biologists, 2011)
In recent years, plants have been developed as an alternative expression system to mammalian hosts for the production of therapeutic proteins. Many modifications to the plant glycosylation machinery have been made to render it more human because of the importance of glycosylation for functionality, serum half-life, and the safety profile of the expressed proteins. These modifications include removal of plant-specific β1,2-xylose and core α1,3-fucose, and addition of bisecting N-acetylglucosamine, β1,4-galactoses, and sialic acid residues. Another glycosylation step that is essential for the production of complex human-type glycans is the synthesis of multiantennary structures, which are frequently found on human N-glycans but are not generated by wild-type plants. Here, we report both the magnICON-based transient as well as stable introduction of the α1,3-mannosyl-β1,4-N-acetylglucosaminyltransferase (GnT-IV isozymes a and b) and α1,6-mannosyl-β1,6-N-acetylglucosaminyltransferase (GnT-V) in Nicotiana benthamiana plants. The enzymes were targeted to the Golgi apparatus by fusing their catalytic domains to the plant-specific localization signals of xylosyltransferase and fucosyltransferase. The GnT-IV and -V modifications were tested in the wild-type background, but were also combined with the RNA interference-mediated knockdown of β1,2-xylosyltransferase and α1,3-fucosyltransferase. Results showed that triantennary Gn[GnGn] and [GnGn]Gn N-glycans could be produced according to the expected activities of the respective enzymes. Combination of the two enzymes by crossing stably transformed GnT-IV and GnT-V plants showed that up to 10% tetraantennary [GnGn][GnGn], 25% triantennary, and 35% biantennary N-glycans were synthesized. All transgenic plants were viable and showed no aberrant phenotype under standard growth conditions.